Development of Palm Oil Production and Sales Monitoring System Based On Android - Chikal Fachdiana; Rafie Novianto Sudrajat; Alfian Akbar Gozali (Research Group of Data Engineering, Faculty of Informatics, 2024)
Palm oil is one of the most widely used vegetable oils in the world. It is used as a raw material for the economic area and contributes to foreign exchange earnings. The palm oil enterprise performs a critical position in Indonesia's economic development, lowering poverty and creating different businesses supporting the enterprise. This paper aims to assist in improving forecasting, essential factor identification, early caution structures, overall performance monitoring, and decision help for bunches of palm production. in this paper, a machine based totally on system learning is created and applied in order to estimate palm production using models with algorithm decision tree and timeseries.